2021
DOI: 10.1080/19490976.2021.1902718
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles of Fusobacterium nucleatum compromise intestinal barrier through targeting RIPK1-mediated cell death pathway

Abstract: Microbial factors that mediate microbes-host interaction in ulcerative colitis (UC), a chronic disease seriously affecting human health, are not fully known. The emerging oncobacterium Fusobacterium nucleatum (Fn) secretes extracellular vesicles carrying several types of harmful molecules in the intestine which can alter microbes-host interaction, especially the epithelial homeostasis in UC. However, the mechanism is not yet clear. Previously, we isolated EVs by the ultracentrifugation of Fn culture media and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 45 publications
(37 reference statements)
1
60
0
Order By: Relevance
“…Fourth, like other gram-negative bacteria, F. nucleatum can release extracellular vesicles (EVs) or outer membrane vesicles (OMVs) ( Liu et al, 2019 ; Liu L. et al, 2021 ), which contain a large number of bioactive substances and participate in bacteria-bacteria or bacteria-host cells communications ( Macia et al, 2019 ). By isolating and purifying F. nucleatum (ATCC 23726)-derived EVs, researchers verified that EVs’ surface protein, FomA, could bind to TLR2 on the intestinal epithelial cells and then modulate innate immunity ( Martin-Gallausiaux et al, 2020 ).…”
Section: The Biological Characteristics Of F Nucleatummentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, like other gram-negative bacteria, F. nucleatum can release extracellular vesicles (EVs) or outer membrane vesicles (OMVs) ( Liu et al, 2019 ; Liu L. et al, 2021 ), which contain a large number of bioactive substances and participate in bacteria-bacteria or bacteria-host cells communications ( Macia et al, 2019 ). By isolating and purifying F. nucleatum (ATCC 23726)-derived EVs, researchers verified that EVs’ surface protein, FomA, could bind to TLR2 on the intestinal epithelial cells and then modulate innate immunity ( Martin-Gallausiaux et al, 2020 ).…”
Section: The Biological Characteristics Of F Nucleatummentioning
confidence: 99%
“…By isolating and purifying F. nucleatum (ATCC 23726)-derived EVs, researchers verified that EVs’ surface protein, FomA, could bind to TLR2 on the intestinal epithelial cells and then modulate innate immunity ( Martin-Gallausiaux et al, 2020 ). F. nucleatum EVs’ can also disrupt the intestinal epithelial barrier by activating the FADD-RIPK1-caspase3 signaling pathway to promote necrosis of intestinal epithelial cells ( Liu L. et al, 2021 ). Furthermore, Engevik et al (2021) used OMVs isolated from F. nucleatum (ATCC 10953) to stimulate colonic epithelial cells and found the production of the proinflammatory cytokines IL-8 and TNF increased.…”
Section: The Biological Characteristics Of F Nucleatummentioning
confidence: 99%
“…It has been reported that F. nucleatum -derived EVs induce inflammation via TLR2 pathway in intestinal epithelial cells (IECs), and these effects are similar to those observed with whole F. nucleatum bacteria on IECs [ 29 ]. Other studies also demonstrated that F. nucleatum -derived EVs markedly promoted epithelial barrier loss and oxidative stress in Caco-2 cells [ 30 ] and induced intestinal inflammation [ 31 ]. We first isolated EVs from F. nucleatum and investigated their effect on CRC proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The results of co-immunoprecipitation studies revealed the interaction between RIPK1 and RIPK3 in F. nucleatum OMVs-treated cells. This was abrogated by anti-TNF-α or Nec-1, indicating that F. nucleatum -OMVs upregulate RIPK1 and RIPK3 and promote formation of the necrosome, ultimately causing necroptosis and impairing epithelial barrier function ( 76 ).…”
Section: Potential Role For Panoptosis During Oral Infectious Diseasesmentioning
confidence: 99%